Effective Online Teaching of Recount Texts: Challenges and Implications for Eighth-Grade Students: Pengajaran Online yang Efektif untuk Teks Cerita Ulang: Tantangan dan Implikasi untuk Siswa Kelas Delapan - Yulianti, Eva Anggi; Taufiq, Wahyu (Universitas Muhammadiyah Sidoarjo, 2023)
The COVID-19 pandemic has drastically transformed education in Indonesia, with schools shifting from traditional classrooms to remote learning. This research aims to explore the teacher's approach to online teaching of recount text material and its impact on eighth-grade students' listening skills at SMP Negeri 1 Wonoayu. Employing a descriptive qualitative research method, data was collected through interviews and observations. The findings reveal that students effectively learned through listening to recount text materials, as evidenced by exercise scores. Communication between teachers and students occurred via WhatsApp Messenger Group, while recount text materials were delivered through YouTube videos. However, challenges faced by English teachers included technical understanding, selecting appropriate online listening methods, and motivating students for virtual learning. The research concludes that online teaching of recount texts can be successful but requires addressing these challenges for enhanced effectiveness in remote learning environments. Highlight: The research investigates the impact of the COVID-19 pandemic on education in Indonesia, leading to a shift from classroom-based learning to online learning for eighth-grade students at SMP Negeri 1 Wonoayu. Descriptive qualitative research is employed to explore the teacher's approach to online teaching of recount text materials and its effectiveness in enhancing students' listening skills. The findings demonstrate that students effectively learn through listening to recount text materials, supported by exercise scores, and the use of communication media such as WhatsApp Messenger Group and YouTube videos. However, challenges persist, including the lack of clear assignment timelines and the need to address technical understanding and student motivation in online classes. Keyword: COVID-19 Pandemic, Online Learning, Recount Text, Listening Skills, Eighth-Grade Students.